Primary intraosseous desmoplastic small round cell tumor of the calvarium: Case report and review of the literature - Vadim Khachaturov, MD; Roth W. Christopher; Jacob R. Hodge, MD; John Joseph Doyle, MD; Darren J. Leitao, MD; Camelia Stefanovici, MD; Karen Fritchie, MD (Elsevier, 2015)
Desmoplastic small round cell tumor (DSRCT) is a rare, aggressive malignancy typically occurring intra-abdominally in young adolescent males. Rare extra-abdominal primaries have been reported in the mediastinum, head and neck area, central nervous system, paratesticular region, visceral organs, and soft tissue. We report a primary intraosseous DSRCT of the calvarium in a 6-year-old male who presented with right ear pain and swelling. Imaging showed an aggressive-appearing permeative mixed lytic and sclerotic lesion of the right sphenoid and temporal bones with extensive periosteal reaction, clinically concerning for osteosarcoma. An open biopsy was performed, and the tumor was composed of primitive round cells with perinuclear cytoplasmic clearing, arranged in diffuse sheets and ill-defined nests and surrounded by a prominent desmoplastic stroma. Immunohistochemically the tumor cells were reactive for desmin (dot-like), CD99 (membranous) and cytokeratin AE1/3 (focal). EWSR1-WT1 chimeric fusion transcript was detected by reverse transcriptase-polymerase chain reaction. Sequencing of the fusion transcript revealed a rare in-frame junction of EWSR1 exon 10 to WT1 exon 8. This is the third documented case of an intraosseous DSRCT with molecular confirmation, but it is the first reported case to arise in the calvarium. While the diagnosis of DSRCT is usually straightforward in the classic clinical setting of an intra-abdominal mass, awareness that this entity may present as a bone primary is necessary to prevent misclassification as osteosarcoma or other malignancy.